GENETIC VARIABILITY STUDIES FOR QUALITATIVE AND QUANTITATIVE TRAITS IN F2 GENERATION OF AROMATIC RICE (Oryza sativa L.) - M.H.V BHAVE, L. KRISHNA, CH. SURENDER RAJU, S. SUDHEER KUMAR, S. NARENDER REDDY and (The Journal of Research, PJTSAU, 2017)
F2 generations of 28 crosses were evaluated for the genetic parameters in rice. The estimates of GCV were lower than the respective PCV, indicating the influence of environmental factors on the expression of the quantitative and qualitative traits studied. The phenotypic and genotypic coefficients of variation were high for no. of filled grains/panicle and grain yield per plant. High heritability along with medium to high genetic advance was noticed for the traits viz., days to 50% flowering, 1000 grain weight and most of the kernel traits and these characters can be improved by direct selection and inter-mating superior genotypes in segregating population.